Layer‐based RED‐FEC (L‐RED‐FEC) method for wireless scalable video streaming. Issue 20 (1st September 2014) - Ha, H.; Yim, C.
Abstract : A layer‐based random early detection (RED) forward error correction (FEC) method for scalable video streaming over wireless networks is proposed. The proposed method determines the FEC rate in accordance with the layer‐based error propagation effect as well as network traffic load. Furthermore, a packet importance model based on layer information of scalable video coding (SVC) has been developed for efficient FEC assignment considering the video quality. Simulation results show that the proposed method achieves higher peak signal‐to‐noise ratio (PSNR) values compared with the conventional FEC schemes under various network conditions.